Value at risk and bank capital management - Saita, Francesco (Amsterdam ; Boston : Elsevier Academic Press, 2007)
While the highly technical measurement techniques and methodologies of Value at Risk have attracted huge interest, much less attention has been focused on how Value at Risk and the risk-adjusted performance measures such as RAROC or economic profit/EVA can be effectively used to improve a bank's decision making processes. Academic books are typically concerned primarily with measurement techniques, and devote only a small section to describing the applications, usually without discussing the problems that changing organizational processes in banks may have on business units' behaviour. Practitioners{Lstrok}{OElig} books are often based on a single experience, presenting the approach that has been pursued by a single bank, but often do not adequately evaluate that approach. In actual practice, the choice of how to use Value at Risk and risk-adjusted performance measures has no single optimal solution, but requires effective decision making that can identify the solution that is consistent with the bank's style of management and coordination mechanisms, and often with characteristics of individual business units as well. In this book, Francesco Saita of Bocconi University argues that even though risk measurement techniques have greatly improved in recent years for market, credit and now also operational risk, capital management and capital allocation decisions are far from becoming purely technical and mechanical. On one hand, decisions about capital management must consider handling different capital constraints (e.g. regulatory vs. economic capital ) and face remarkable difficulties in providing a measure of aggregated{middot} Value at Risk (i.e. a measure that considers the overall value at risk of the bank after diversification across risk types). On the other hand, the aim of using capital more efficiently through capital allocation cannot be achieved only through a sort of centralized asset allocation process, but rather by designing a Value at Risk limit system and a risk-adjusted performance measurement system that are designed to provide the right incentives to individual business units. This connection between sophisticated and cutting edge risk measurement techniques and practical bank decision making about capital management and capital allocation make this book unique and provide readers with a depth of academic and theoretical expertise combined with practical and real-world understanding of bank structure, organizational constraints, and decisionmaking processes. *Contains concise, expert analysis of the latest technical VaR measures but without the highly mathematical component of other books *Discusses practical applications of these measures in the real world of banking, focusing on effective decision making for capital management and allocation *Author is based at Bocconi University in Milan, Italy, one of the foremost institutions for banking in Europe.
Value at risk, capital management, and capital allocation -- What is 'capital' management? -- Market risk -- Credit risk -- Operational risk and business risk -- Risk capital aggregation -- Value at risk and risk control for market and credit risk -- Risk-adjusted performance measurement -- Risk-adjusted performance targets, capital allocation, and the budgeting process.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Bank capital; Banks and banking -- Risk management; Electronic books